PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV DI SD INPRES PERUMNAS 2 KOTA KUPANG TAHUN AJARAN 2016/2017 - YEFTA BAKO (Program Studi Pendidikan Seni Rupa Fakultas Keguruan dan Ilmu Pendidikan Universitas Muham, 2018)
This study was conducted to find out the use of image media at the learning orientation stage is very helpful to the effectiveness of the learning process and delivery of the contents of the lesson at that time, the image media can channel the message from the source to the recipient (student). Once cultivated the interest of students to learn actively in the classroom as well as improve student achievement. This research is inseparable from the theoretical basis, and also to obtain data by using observation, documentation and test techniques. The purpose of the purpose in this study is to determine the use of image media in improving the motivation of learning in fourth graders Elementary School Inpres Perumnas 2 Kota Kupang academic year 2016/2017. So the results of research and discussion can be concluded the use of good and interesting learning media can improve student learning motivation. And after application of learning pattern using image media on PAK subject, hence increasing class average this can be seen from prasiklus which is only 41,07% become 68,21% in cycle I and become 83,21% in cycle II. Media images are the most effective learning media used in the learning process because it can improve students' learning motivation through the images presented with interesting and easy to understand by the students.